The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1177/000348949110000415
|View full text |Cite
|
Sign up to set email alerts
|

Syndrome of Inappropriate Antidiuretic Hormone Secretion in Cancer of the Head and Neck

Abstract: The syndrome of inappropriate secretion of arginine vasopressin (AVP) known as the syndrome of inappropriate antidiuretic hormone secretion (SIADH) is characterized by hyponatremia that results from water retention attributable to persistent AVP release. It may occur in a variety of malignant and nonmalignant lesions, with small cell or oat cell carcinoma of the lung by far responsible for the largest number of these cases. Cancer of the head and neck may be a rare cause of SIADH, and only a few such cases hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 12 publications
0
20
0
2
Order By: Relevance
“…Head and neck cancers are responsible for only 1.5% of syndrome of inappropriate secretion of ADH (SIADH) [24] and a rare case report suggested that SIADH can be related to thyroid cancer [27]. In our univariate analysis, we found that lung metastasis had significant association with hyponatremia in moderate to severe group.…”
Section: Discussionmentioning
confidence: 66%
“…Head and neck cancers are responsible for only 1.5% of syndrome of inappropriate secretion of ADH (SIADH) [24] and a rare case report suggested that SIADH can be related to thyroid cancer [27]. In our univariate analysis, we found that lung metastasis had significant association with hyponatremia in moderate to severe group.…”
Section: Discussionmentioning
confidence: 66%
“…No correlation was found between lymphatic nodal status and the syndrome. 4–6,10,11 Our results indicate that the two parameters correlate, but without statistical proof ( P = .1231).…”
Section: Discussionmentioning
confidence: 62%
“…Previous studies have suggested a connection between disease recurrence and the syndrome 2,6,10,11 although no connection was statistically significant. 5 Our results did not show any correlation between disease recurrence and the syndrome.…”
Section: Discussionmentioning
confidence: 81%
“…Although the prognosis of patients with paraneoplasti c syndromes associated with laryngeal cancer is poor (80), we believe that knowledge of these syndromes is important for diagnosis and treatment. In particular, water restriction and parenteral sodium chloride may be suf cient for overcoming the acute phase of the syndrome of inappropriate antidiuretic hormone secretion (81).…”
Section: Paraneoplastic Syndromesmentioning
confidence: 99%